HYPERMOBILITY: A RISK FACTOR FOR FAILURE FOLLOWING ACL RECONSTRUCTION. Issue 17 (24th October 2013) - Akhtar, MA; Ashton, F; Keating, JF
Abstract : Hypermobility is associated with increased risk of sporting injuries. This study was performed to assess the risk of failure following primary ACL reconstruction in patients with hypermobility. Prospective data were collected for 28 patients undergoing primary ACL reconstruction between October 2008 and July 2009 including demographic details, sports played, hypermobility and Benign Joint Hypermobility Syndrome (BJHS). Electronic records from emergency and orthopaedic departments were checked in April 2013 for failure of ACL reconstruction. Beighton score of 4 or above was used to diagnose hypermobility. Brighton criteria were used to diagnose BJHS. The mean age was 27 y (range 15–54). There were 19 males and 9 females. 24 patients (86%) were involved in contact sports and football was the most common sport played in 9 patients (37%). The mean Beighton score for these patients was 2.8 (range 0–9). 10 patients (36%) in this group had a Beighton score of 4 or more indicating hypermobility (Group A). 18 patients (64%) had Beighton score less than 4 (Group B). The mean age for Group A (10 patients) was 26 years (range 14–40). There were 4 male and 6 females. 9 patients were involved in contact sports. 3 patients (30%) had failure of ACL reconstruction. The mean Beighton score for these patients was 5.9 (range 4–9). 3 patients (30%) had BJHS. The mean age for Group B (18 patients) was 28 years (range 15–54). There were 15 males and 3 females. 15 patients were involved in contact sports. The mean Beighton score was 1 (range 0–3). No patient had failure of ACL reconstruction. Hypermobile patients had a higher incidence of failure of ACL reconstruction (30% vs 0%). 30% patients fulfilled the Brighton criteria for BJHS. These factors should be assessed before ACL reconstruction to select the appropriate graft. Further studies are needed to decide the best graft for ACL reconstruction in the presence of hypermobility.